The Self-efficacy of Female Mathematics Teachers in the Primary Stage According to the Scientific Qualification (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the self-efficacy of mathematics teachers in the primary stage and its relationship to their academic qualifications.The two researchers prepared a scale of self-efficacy consisting of (45) items, which was applied as of Sunday 5/12/2021 and completed on Sunday corresponding to 16/1/2022 on a sample of mathematics teachers in the primary school consisting of (305) female teachers from the governorate Diyala - Baquba District, and the opinions of (30) female teachers were surveyed without the application sample, while the construction sample consisted of (450) female teachers.The results of the research showed that the academic qualification has a positive role in the mathematics teachers' possession of self-efficacy, and the results related to teaching mathematics have shown that self-efficacy has a positive role in that.The research recommended several recommendations, including holding training workshops for female teachers to enhance their self-efficacy belief and increase their self-efficacy.